Aestheticization and its consequences: A study on school teachers - Mathushan, P.; Nanthagopan, Y. (University of Jaffna, 2020)
Unprecedentedly, aestheticization exponentially plays a dramatic role in organisational studies and the scholarship on the space, place and aestheticization has been far less focused and remained agnostic. The present study aims at discovering the effect of space, place and aestheticization among teachers. Lucidly there is an urge to explore and investigate how the school's physical environment and its design have been athetized and how its effect on the teacher’s feelings. With the aid of the purposive sampling technique, data were garnered from teachers working in primary and secondary schools with in-depth interviews. Drawing on conceptual insights from organizational aesthetics and theory of satisfaction and motivation, this qualitative study explored the relationship between workplace design aesthetics, school teacher’s satisfaction and motivation. The majority of the informants interviewed agreed that space, place and aestheticization have a strong effect on employee satisfaction, mood, feeling, involvement, creativity and motivation. Aesthetics seem to be a predominantly vital factor in predicting productivity and performance.
Keywords: Aestheticization; Education; Motivation; Performance; Place; Satisfaction and space